Site occupancy and habitat selection of cheetahs Acinonyx jubatus (Shreber, 1775) in a human-influenced landscape in Mozambique - Somers, Michael J. (University of Pretoria, 2021)
Dissertation (MSc (Wildlife Management))--University of Pretoria, 2013.